Ferroptosis-related oxidative stress activation in the acute phase of Kawasaki disease - Xue, Xing; Dai, Guangan; Lin, Yixiang; He, Lan; Sheng, Wei; Sun, Jingwei; Liu, Fang (Frontiers in Immunology, 2025)
IntroductionKawasaki disease (KD) is an acute systemic vasculitis with unclear etiology and pathogenesis. Emerging evidence suggests a potential role of ferroptosis in various cardiovascular diseases. Therefore, this study aimed to explore and validate the involvement of ferroptosis in the pathogenesis of KD.MethodsPeripheral blood samples were collected from 10 patients with KD and 10 febrile controls (FC) were collected for RNA sequencing. Differentially expressed genes (DEGs) were identified and subjected to pathway enrichment analysis. Ferroptosis-related DEGs were further validated in patient samples. In vitro, THP-1-derived macrophages (THP-1-Mφs) were stimulated with sera from KD patients to assess intracellular Fe2+ accumulation, lipid reactive oxygen species (lipid ROS) levels, mitochondrial membrane potential, and mitochondrial ultrastructural changes. Liproxstatin-1, a specific ferroptosis inhibitor, was applied to determine whether the ferroptosis-related alterations were reversible.ResultsTranscriptomic analysis revealed significant enrichment of DEGs in the ferroptosis pathway. Validation experiments confirmed a trend toward ferroptosis activation in KD patients. In vitro, THP-1-Mφs treated with KD sera exhibited increased intracellular Fe2+ and lipid ROS levels, impaired mitochondrial membrane potential, and characteristic mitochondrial morphological alterations associated with ferroptosis. Notably, these ferroptosis-related changes were attenuated by Liproxstatin-1 treatment.ConclusionOur findings indicate that ferroptosis is activated in KD and may contribute to its pathogenesis. Ferroptosis inhibitor alleviated the associated cellular damage, suggesting that it may represent a potential therapeutic strategy for KD.